2015
DOI: 10.1007/s11103-015-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of GmTOE4a in the regulation of photoperiod-mediated flowering and plant morphology in soybean

Abstract: Flowering time, maturity, and plant morphology have considerable effects on the adaptation and grain yield of soybean (Glycine max). The identification of novel genes and an understanding of their molecular basis are critical to improve soybean productivity. In this study, we cloned a flowering time related APETALA2-like gene GmTOE4a and generated GmTOE4a-overexpressing lines in the cultivar Williams 82. The transgenic lines exhibited late flowering both under long day and short day conditions, and repressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…The soybean genome possesses a total of ten FT orthologs, among which six retain the FT function and can promote flowering of Arabidopsis ft mutants [ 22 , 23 ] or Col-0 [ 24 , 25 ]. All of the six homologs could therefore function as potential floral inducers in soybean, although only two of them, FT2a and FT5a , have been extensively characterized in studies of molecular mechanisms of flowering [ 15 , 19 , 22 , 24 , 26 28 , 40 , 43 ]. This study demonstrates that different levels of FT2a expression directly regulate natural variation in flowering time in soybean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soybean genome possesses a total of ten FT orthologs, among which six retain the FT function and can promote flowering of Arabidopsis ft mutants [ 22 , 23 ] or Col-0 [ 24 , 25 ]. All of the six homologs could therefore function as potential floral inducers in soybean, although only two of them, FT2a and FT5a , have been extensively characterized in studies of molecular mechanisms of flowering [ 15 , 19 , 22 , 24 , 26 28 , 40 , 43 ]. This study demonstrates that different levels of FT2a expression directly regulate natural variation in flowering time in soybean.…”
Section: Discussionmentioning
confidence: 99%
“…Various combinations of mutations that occur independently at E1 , E3 , and E4 lead to insensitivity or low sensitivity of flowering to photoperiod [ 29 , 30 ]. Besides the above four genes, a number of soybean orthologs of Arabidopsis flowering genes have been characterized: COL ( CO-like ) [ 25 , 31 ], CRY ( CRYPTOCHROME ) [ 32 , 33 ], FKF1 [ 34 ], FLD ( FLOWERING LOCUS D ) [ 35 ], FUL ( FRUITFULL ) [ 36 ], RAV - like ( RELATED TO ABI3/VP1 - like ) [ 37 ], SOC1 / AGL20 ( SUPPRESSOR OF OVEREXPRESSION OF COL1/AGAMOUS-LIKE 20 ) [ 38 , 39 ], TARGET OF EAT1 ( TOE ) [ 40 ], and ZTL ( ZEITLUPE ) [ 41 ]. A genome-wide association study also revealed a number of SNPs that were significantly associated with flowering time; some of these SNPs implied an involvement of orthologs to Arabidopsis flowering genes, such as EARLY FLOWERING 8 and SOC1 or AGAMOUS-LIKE 6 , in the control of flowering time in soybean [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrates that GmSBH1 is required for maintaining growth and development in soybean [11]. Overexpression of a flowering time-related APETALA2-like gene GmTOE4a caused late flowering and altered soybean plant morphology (increased stem thickness and reduced plant height, internode length and leaf size) [12], demonstrating that the gene plays a role in the regulation of the photoperiodic flowering pathway in soybean. The miR156 and miR172, microRNA genes, are known to be associated with vegetative phase change.…”
Section: Characterization and Definition Of Soybean Plant Architecturementioning
confidence: 77%
“…By analyzing the inner relationships between the genotype and phenotype of a crop, scientists are able to modify the gene sections and thereby improve yields. Crop genetic breeding is a currently a significant research field of interest, and great results have thus far been achieved [4][5][6][7][8]. Compared to genotypes, the phenotype methods have developed much slower [9].…”
Section: Introductionmentioning
confidence: 99%